Don't shoot the messenger: How business leaders get their bearings on a matter of science. (June 2016) - Bowden, Vanessa; Leahy, Terry
The views of business leaders are of particular interest where climate change policies are concerned. This is a study based on interviews with business leaders in the Hunter region. The sociological literature suggests either that the business community will be split according to industry, or that the business community as a whole will resist regulation. Our study finds differences of opinion in the business community somewhat marginal. Interviewee responses also suggest the importance of considering the class location of those who are the messengers of climate science – scientists and environmentalists. Business reactions come out of the habitus of business people and their animosity towards those with high cultural capital. This becomes a barrier to full acknowledgement of the implications of climate science.